Application of prediction tools in patients with IgA nephropathy : single center cohort - Riesenberger, João Rodriguez Rios (2023)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2023